Biomechanical effects of angular stable locking in intramedullary nails for the fixation of distal tibia fractures. (November 2016) - Augat, Peter; Hoegel, Florian; Stephan, Daniel; Hoffmann, Stephanie; Buehren, Volker
Treatment of distal tibia shaft fractures using intramedullary nailing requires stable fixation of the distal fragment to prevent malunion. Angular stable locking for intramedullary nails pledge to provide increased mechanical stability. This study tested the hypothesis that intramedullary nails with angular stable interlocking screws would have increased construct stiffness, reduced fracture gap movement and enhanced fatigue failure compared to nails with conventional locking having the same diameter. Biomechanical experiments were performed on 24 human cadaveric tibiae which obtained a distal fracture and were fixed by three different techniques: conventional locking with 8- and 10-mm-diameter nails and angular stable locking with 8-mm nails. Stiffness of the implant–bone construct and movement of the fragments were tested under axial loading and torsion. The constructs were tested to failure under cyclic fatigue loading. Analysis of variance and Kaplan–Meier survival analysis were used for statistical assessment. Axial stiffness of the 10-mm nail was about 50% larger compared to both 8-mm nail constructs independent of the type of locking mode (p < 0.01). No differences were found in axial performance between angular stable and conventional locking neither under static nor under cyclic testing conditions (p > 0.5). Angular stability significantly decreased the clearance under torsional load by more than 50% compared to both conventionally locked constructs (p = 0.03). However, due to the larger nail diameter, the total interfragmentary motion was still smallest for the 10-mm nail construct (p < 0.01). Although the 10-mm nail constructs survived slightly longer, differences between groups were minor and not statistically significant (p = 0.4). Our hypothesis that angular stable interlocking of intramedullary nails would improve mechanical performance of distal tibia fracture fixation was not confirmed in a physiologically realistic loading scenario. Whether minor mechanical advantages provided by angular stability of the locking screws would improve biological tissue response cannot be concluded from this biomechanical study.